MORALITY ASPECTS IN THE FILM OF “FERDINAND” BY CARLOS SALDANHA - Arifka Noor Mirsawati; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2020)
The purpose of this study was to know 1) Types of moral aspects contained. 2) The dominant moral aspect is found. 3) Correlation of morality aspects with a sociological approach to literature. The research method used to analyze this film is a qualitative method that contains two elements, namely intrinsic elements in characters and characterizations as in morals through the approach of literary sociology. Based on the results of the study it can be concluded that 1) There are 7 moral aspects found in the “Ferdinand” film based on Michelle Borba's theory, namely Empathy, Conscience, Self-Control, Respect, Kindness, Tolerance, Justice. 2) The dominant moral aspects found were kindness (11 data), empathy (6 data), conscience (5 data), and self control (5 data). 3) the correlation of morality aspects with the approach of literary sociology, both of which highlight the conditions and social problems that are taking place in social life.